The derivative concept of legal interpretation - Białkowski, Michał (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2015)
The dominant thinking on legal interpretation in contemporary Polish legal doctrine is the derivative concept of interpretation of Professor Maciej Zieliński. One of the most important features of this concept is that it distinguishes legal provision from legal norm. Legal provision is the statement of the fundamental text of the legal act taken from dot to dot, whereas legal standard is the standard of conduct which was established or recognised by the authorised body of the state, in the traditional jurisprudence of the tripartite structure (hypothesis–instruction–sanction). The derivative concept of legal interpretation also rejects the principle clara non sunt interpretanda and replaces it with the principle omnia sunt interpretanda. But the most derivative part of the concept is the accurate identification of features of the language of Polish legal texts, such as its specific variability as it takes place somehow beyond the legal text. Among other features characteristic of Polish legal texts we could mention that they are written at a ‘descriptive level’ and read at a ‘normative level’ (the quasi-idiomacity of Polish legal texts), the fragmentation of legal standards (above all syntactic and semantic) and the presence of vague or imprecise turns of phrase.. M. Zieliński grouped directives of interpretation in his concept into three phases : ordering, reconstructive and perceptual. According to M. Zieliński legal interpretation starts with the determination of the state of the law applicable to the case and of the content of the interpreted provision. The aim of the second (reconstructive) phase is to obtain the standard expression including the determination of the recipient (subject to which the order or prohibition of action is applied) and the determination of the circumstances in which the specified behaviour is ordered or prohibited. The standard expression after this phase does not yet constitute the legal standard owing to its potential ambiguity, which is finally clarified in the perceptual phase of interpretation.
Keywords: legal interpretation; theory of law; derivative concept of legal interpretation; principle clara non sunt interpretanda; legal provision